A Case "Fore" Buffer Zones - Natalie Bird; Nicholas Schlereth (Journal of Applied Sports Management, 2020)
Golf tournaments are fun and exciting events because they allow for up-close interaction with players, but they also present a risk management concern. Professional golfers are not immune to hitting errant golf shots and a lack of buffer zones often results in spectator injury. The purpose of this paper is to examine how buffer zones can be enhanced or developed to protect patrons. Utilizing data from the PGA Tour, a model was developed to aid in predicting errant tee shots to enhance buffer zones.
Keywords: Golf; Patrons; PGA; Safety; Sport Management